Pengaruh Kualitas Produk, Celebrity Endorser, dan Brand image Terhadap Keputusan Pembelian Produk Facial Wash KAHF (Studi pada Konsumen Produk Facial Wash KAHF di Kabupaten Jombang) - Ahmad Mujahidin Syifa’; Nurhajati Nurhajati; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study aims to analyze the effect of product quality, celebrity endorser, and brand image on purchasing decisions of KAHF facial wash products in Jombang Regency. This research uses a quantitative approach with an explanatory research design. The population consists of consumers who have purchased and used KAHF facial wash products in Jombang Regency. The sampling technique used was purposive sampling with a total of 120 respondents. Data were collected through questionnaires measured using a Likert scale and analyzed using multiple linear regression analysis with SPSS. The results show that product quality, celebrity endorser, and brand image simultaneously have a significant effect on purchasing decisions. Partially, product quality, celebrity endorser, and brand image each have a positive and significant effect on purchasing decisions. These findings indicate that improving product quality, selecting appropriate celebrity endorsers, and strengthening brand image can enhance consumer purchasing decisions. Keywords: Product Quality, Celebrity Endorser, Brand Image, Purchase Decision